Renal evaluation in patients with type 2 diabetes mellitus and its association with diastolic blood pressure (Faculty of Medicine Universitas Indonesia, 2016)
Background: HbA1c is correlated with the estimated glomerular filtration rate (eGFR) and diastolic blood pressure (DBP). Our main objective was to evaluate the trend of biochemical and clinical variables, in relation to the eGFR in patients with type 2 diabetes mellitus (T2DM). Methods: This was a retrospective, longitudinal, and descriptive study, including patients with T2DM, who were cared for from January 2014 until December 2014, at the Clínica de Diabetes, Hospital Regional “Gral. Ignacio Zaragoza